Non-Observance of Maxims in Facebook Conversation (A Case Study in English Education Department) - Irma Rizkiani Hanifah (Universitas Pendidikan Indonesia (UPI), 2013)
This study was aimed at investigating types of maxims which are not observed by male and female Facebook users and how male and female users fail to observe a maxim in their conversation. This study involved 16 male and 15 female students majoring in English at one university in Bandung who have Facebook account. This study applied qualitative case study method. The data were in the form of conversations in Facebook that were downloaded from August until December 2012. The data were collected through several considerations of non-observance of maxims within the conversation based on Grice’s theory of conversational implicature. The collected data are analyzed through several procedures of identifying, classifying, calculating, and interpreting. The findings showed that male users commonly failed to observe the maxim of relation by giving irrelevant contribution (53.13%), while female users commonly failed to observe the maxim of quantity by giving more information (44%). In addition, flouting of maxim is the most frequent non-observance of maxim that was performed by both male and female users in their conversation (96.88% 92%). Thus, both users tended to make a joke, to stay close with friends, or just to contribute the conversation when they performed such non-observance of maxims.Keywords: Non-observance of Maxims, Facebook, Conversation, Cooperative Principle, Implicature